Early Detection Methods for Pine Wood Nematode Infections of Maritime Pine in Portugal - Bonifácio,Luis (2011)
Four different techniques for early detection of pines infected by the pine wood nematode (Bursaphelenchus xylophilus) were tested in the maritime pine within the affected zone of Setúbal peninsula, in Portugal. From the four methods tested, the wood electrical resistance only had significantly different readings from healthy pines when the tree was already visually decayed. The sap flow measurements made in six previously selected pines didn't allow any conclusion, because none of the pines died during the survey. The oleoresin flow, induced using a punch hole in the trunk, with 14cm diameter, at 1.30m height, proved to be reliable for detecting an infected pine, when there is a complete absence of resin production (99% of the observations). The flow ceases about one and a half months before decay symptoms are obvious (when over 25% of the pine's needles are yellow).